5S Culture in Strengthening the Character Education of Students at SD Negeri Manggong Lombok Tengah - Windi Asmawati; Hotimah Hotimah; Sarwin Hidayat; Ita Lestari; Sri Endang; Lalu Sumardi; Edy Herianto (International Journal of Education and Digital Learning (IJEDL), 2024)
This research aims to describe the planning, implementation and impact of implementing the 5S culture in strengthening the character education of students at Manggong State Elementary School, Central Lombok. This research uses a qualitative research approach with an inductive approach. The subjects of this research were all students, teachers and principals at SD Negeri Manggong. Data collection techniques use observation, interviews and documentation. The data analysis used was data analysis from Milles and Huberman which consisted of data analysis, data presentation and drawing conclusions. The results of this research show that the implementation of strengthening character education through 5S culture at SD Negeri Manggong, Central Lombok was carried out with good planning and then implementing or getting used to 5S behavior, namely Smiling, Greeting, Greeting, Polite and Polite. In implementing character values ​​through 5S culture, positive character values ​​have begun to appear, including shaking hands or shaking hands and saying hello to teachers when entering the school gate, speaking polite words and behaving politely between teacher and teacher, teacher and students. and between fellow students.